2010
DOI: 10.1007/s10461-010-9715-y
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Disclosure of Their HIV Infection to Their Children in the Context of the Family

Abstract: We interviewed 33 HIV-infected parents from the HIV Cost and Services Utilization Study (HCSUS), 27 of their minor children, 19 adult children, and 15 caregivers about the process of children learning that their parents were HIV positive. We summarize the retrospective descriptions of parents’ disclosure of their HIV status to their children, from the perspective of multiple family members. We analyzed transcripts of these interviews with systematic qualitative methods. Both parents and children reported unpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
106
4
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(135 citation statements)
references
References 33 publications
16
106
4
9
Order By: Relevance
“…Subsequently, parents and children can support each other (Ishikawa et al, 2011;Kennedy et al, 2010;Madiba & Matlala, 2012;Rwemisisi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, parents and children can support each other (Ishikawa et al, 2011;Kennedy et al, 2010;Madiba & Matlala, 2012;Rwemisisi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The successful delivery of full disclosure is crucial to sustaining a good family environment post disclosure, and prior researchers have advocated for parents incapable of performing disclosure on their own to seek help from HCPs, friends, or extended family members (Bikaako-Kajura et al, 2006;De Baets et al, 2008;Heeren et al, 2012;Kennedy et al, 2010;Kouyoumdjian, Meyers, & Mtshizana, 2005;Nam et al, 2009). It is interesting to note that most HIV-positive children preferred to receive disclosure from a HCP trained in disclosure delivery rather than a parent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, hiding it has three faces: the non exteriorization of HIV/ AIDS, the seropositivity of the mother and child. All with consequences that are difficult to face, demanding care (21) . The time and manner in which the mother and/ or other family member will reveal the diagnosis to the child is of great importance, since the traumas in infancy may compromise its future.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Kennedy (2010), found that, when children learned about their mothers' HIV infection, their reactions varied from manifestations of emotional support and closeness to denial and anger. In that same study, one participant expressed anger toward his father, the source of his mother's HIV infection.…”
Section: Transition To Adulthood: Becoming a Parentmentioning
confidence: 99%